2011
DOI: 10.1203/pdr.0b013e3182042a20
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Ovine Fetal Cortisol Response to Stress

Abstract: This study tested the hypothesis that the sexually dimorphic adrenocortical response to stress is already established before birth. Chronically instrumented late gestation pregnant sheep carrying 16 male and 15 female age-matched singleton fetuses were subjected to an acute episode of hypoxic stress. Maternal and fetal blood gases, adrenocorticotrophic hormone (ACTH), and cortisol were measured. In addition, six male and six female fetuses received the ACTH analog, Synacthen, and plasma cortisol was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
2
13
1
Order By: Relevance
“…Importantly, Control dams from both generations had unaltered sex ratios. Others have reported that exposure to acute hypoxic stress in ewes resulted in a 2-fold greater concentration of plasma cortisol in male compared with female fetuses (Giussani et al 2011). Taken together with our findings, this suggests that males are more sensitive to adverse in utero exposure.…”
Section: Parametersupporting
confidence: 88%
“…Importantly, Control dams from both generations had unaltered sex ratios. Others have reported that exposure to acute hypoxic stress in ewes resulted in a 2-fold greater concentration of plasma cortisol in male compared with female fetuses (Giussani et al 2011). Taken together with our findings, this suggests that males are more sensitive to adverse in utero exposure.…”
Section: Parametersupporting
confidence: 88%
“…As well as finding a strong trend for male fetuses to have a lower arterial pH than female fetuses, the present study demonstrates that female, but not male fetuses, show a rise in circulating plasma cortisol between 131 and 133 days of gestation under control conditions, which may influence lung maturation. However, in response to maternal hypoxia at 130 days of ovine gestation, the increase in circulating cortisol concentration was twice as great in male fetuses compared with females, which was attributed to a greater adrenocortical sensitivity to adrenocorticotrophic hormone (ACTH) in male fetuses (17). This greater adrenal sensitivity to ACTH in the male fetus has previously been shown in male-female twin pairs (33).…”
Section: Pulmonary Surfactant Compositionmentioning
confidence: 87%
“…Each ion pair was monitored for 10 -50 ms with a resolution of 0.7 atomic mass units at half-peak height and averaged from continuous scans over the elution period. Lipid concentrations were calculated by relation of the peak area of each species to the peak area of the corresponding internal standard (17). Total lipids of each class were calculated by summation of the individual lipid species.…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing literature on the sex-differentiated impact of stress on cortisol. Boys appear more likely than girls to show elevated levels following stress under real-life and laboratory controlled conditions (41), a mechanism that may be in place before birth (42). Might boys be more vulnerable than girls to the neurotoxicity effects of persistently elevated cortisol within the normal range?…”
Section: Discussionmentioning
confidence: 99%